2021
DOI: 10.1021/acs.jafc.1c02294
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate Modulates Immunity, Intestinal Mucosal Barrier Function, and Gut Microbiota in Cyclophosphamide-Induced Immunosuppressed BALB/c Mice

Abstract: This study investigated the protective effects of sodium alginate (SA) on the gut microbiota, immunity, and intestinal mucosal barrier function in cyclophosphamide-induced immunosuppressed BALB/c mice. SA alleviated spleen tissue damage and restored impaired immune functions, such as increasing the immune organ index, decreasing splenic T lymphocytes, and markedly increasing the secretion of serum immunoglobulins and cytokines in immunosuppressed mice. In addition, SA reversed the intestinal mucosal injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 45 publications
(70 reference statements)
5
48
0
Order By: Relevance
“…It was previously reported that the abundance of Marvinbryantia was positively correlated with the level of cecal SCFAs and negatively related to the total antioxidant capacity of liver in LPS-treated mice ( Guo et al, 2021 ). Tyzzerella and Peptococcus are beneficial to inhibit the development of inflammation and ameliorate the host immunity, partly due to the inhibition of the secretion of lipopolysaccharide, D-lactic acid and TNF-α ( Huang et al, 2021b ). It was previously reported that Negativibacillus , belonging to Ruminococcaceae family, possessed the ability of accelerating the production of butyric acid, which provides energy for intestinal epithelial cells ( Huang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that the abundance of Marvinbryantia was positively correlated with the level of cecal SCFAs and negatively related to the total antioxidant capacity of liver in LPS-treated mice ( Guo et al, 2021 ). Tyzzerella and Peptococcus are beneficial to inhibit the development of inflammation and ameliorate the host immunity, partly due to the inhibition of the secretion of lipopolysaccharide, D-lactic acid and TNF-α ( Huang et al, 2021b ). It was previously reported that Negativibacillus , belonging to Ruminococcaceae family, possessed the ability of accelerating the production of butyric acid, which provides energy for intestinal epithelial cells ( Huang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of Oscillibacter had been reported to be negatively associated with obesity, fatty liver, inflammation and insulin resistance ( Thingholm et al, 2019 ). As a controversial harmful bacterium, Desulfovibrionaceae was previously reported to be closely associated with the production of lipopolysaccharide in intestine ( Huang et al, 2021b ). It was previously reported that Clostridium played an important role in colitis induced by oral administration of dextran sulfate sodium, because Clostridium may promote the secretion of inflammatory cytokines ( Zhu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized controlled trial, overweight and obese adults consuming avocado daily for 12 weeks were enriched in the relative abundance of Alistipes compared to the control group ( 89 ). Tyzzerella is considered a pathogenic bacteria in the intestine ( 90 ). Huang et al investigated the protective effects of sodium alginate on the gut microbiota, immunity, and intestinal mucosal barrier function in cyclophosphamide-induced immunosuppressed BALB/c mice, and found that sodium alginate significantly decreased the pathogenic bacteria Tyzzerella in the intestine ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tyzzerella is considered a pathogenic bacteria in the intestine ( 90 ). Huang et al investigated the protective effects of sodium alginate on the gut microbiota, immunity, and intestinal mucosal barrier function in cyclophosphamide-induced immunosuppressed BALB/c mice, and found that sodium alginate significantly decreased the pathogenic bacteria Tyzzerella in the intestine ( 90 ). However, few studies have reported the correlation between Tyzzerella and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Cy is a major component of oncology chemotherapy drugs and is also commonly used to induce immunosuppression in animal models (Chen et al, 2019;Ding et al, 2019b;Cai et al, 2021;Huang et al, 2021). The experimental design was conducted according to the reported by Chen et al, (2019) (Fig.…”
Section: Animals and Experimental Designmentioning
confidence: 99%